Prognostic and clinicopathological significance of miR-638 in cancer patients: A meta-analysis. Issue 15 (16th April 2021) - Hu, Lixia; Huang, Mengqin; Yuan, Qianqian; Kong, Fanliang
Abstract: Introduction: MiR-638 is believed to be involved in human cancers. However, the prognostic value of miR-638 in human carcinomas is controversial and inconclusive. Therefore, we conducted this meta-analysis to investigate the association between miR-638 expression and clinical outcomes in the patients with various cancers. Methods: We searched Pubmed, Embase, Wanfang, and the China National Knowledge Infrastructure (CNKI) up to September 1, 2020 to identify relevant studies. Hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were used to correlate expression of miR-638 with prognosis and clinicopathological features. Results: A total of 18 studies involving 1886 patients were included in the meta-analysis. The results revealed that low miR-638 expression was significantly correlated with poor overall survival (OS) (HR = 2.09, 95% CI: 1.46–2.98, P < .001), but not with disease-free survival (DFS) (HR = 1.71, 95% CI: 0.31–9.56, P = .540). Subgroup analysis found that low miR-638 expression was associated with worse OS in patients with digestive system cancer (HR = 2.47, 95% CI: 1.85–3.30, P < .001), the reported directly from articles group (HR = 2.12, 95% CI: 1.34–3.33, P < .001), survival curves group (HR = 2.02, 95% CI: 1.07–3.80, P = .029), in studies with sample size ≥100 (HR = 2.12, 95% CI: 1.34–3.35, P = .001), and in studies with sample size <100 (HR = 2.02, 95%CI: 1.09–3.75, P = .025). Moreover, cancer patients with low miR-638 expression were prone to tumor size (OR = 1.47, 95% CI: 1.03–2.09, P = .035), earlier lymph node metastasis (present vs absent, OR = 2.26, 95% CI: 1.63–3.14, P < .001), earlier distant metastasis (present vs absent, OR = 2.60, 95% CI: 1.45–4.67, P < .001), TNM stage (III-IV vs I-II, OR = 2.01, 95% CI: 1.35–2.99, P = .001), and portal vein invasion (present vs absent, OR = 4.39, 95% CI:2.23–8.64, P < .001), but not associated with age, gender, tumor differentiation, and vascular invasion. Conclusions: MiR-638 may serve as a promising indicator in the prediction of prognosis and clinicopathological features in patients with different kinds of cancers.